Evasion of Plant Innate Defense Response by Salmonella on Lettuce - Johnson, Nicholas; Litt, Pushpinder K.; Kniel, Kalmia E.; Bais, Harsh (Frontiers in Microbiology, 2020)
To establish host association, the innate immune system, which is one of the first lines of defense against infectious disease, must be circumvented. Plants encounter enteric foodborne bacterial pathogens under both pre- and post-harvest conditions. Human enteric foodborne pathogens can use plants as temporary hosts. This unique interaction may result in recalls and illness outbreaks associated with raw agricultural commodities. The purpose of this study was to determine if Salmonella enterica Typhimurium applied to lettuce leaves can suppress the innate stomatal defense in lettuce and utilization of UD1022 as a biocontrol against this ingression. Lettuce leaves were spot inoculated with S. Typhimurium wild type and its mutants. Bacterial culture and confocal microscopy analysis of stomatal apertures were used to support findings of differences in S. Typhimurium mutants compared to wild type. The persistence and internalization of these strains on lettuce was compared over a seven-day trial. S. Typhimurium may bypass the innate stomatal closure defense response in lettuce. Interestingly, a few key T3SS components in S. Typhimurium were involved in overriding stomatal defense response in lettuce for ingression. We also show that the T3SS in S. Typhimurium plays a critical role in persistence of S. Typhimurium in planta. Salmonella populations were significantly reduced in all UD1022 groups by day seven with the exception of fliB and invA mutants. Salmonella internalization was not detected in plants after UD1022 treatment and had significantly higher stomatal closure rates (aperture width=2.34µm) by day 1 compared to controls (8.5 µm). S. Typhimurium SPI1 and SPI2 mutants showed inability to reopen stomates in lettuce suggesting the involvement of key T3SS components in suppression of innate response in plants. These findings impact issues of contamination related to plant performance and innate defense responses for plants.